Sustainable Innovations in Textile Fibres (Textile Science and Clothing Technology,, 2018)
This book highlights the innovations in textile fibres, that is the starting point of the supply chain. There are numerous innovations made in terms of making the existing fibres sustainable and also to discover new sustainable fibres. This book deals with those innovative sustainable textile fibres in detail. It also presents an overview of various current textile fibres, their issues associated with sustainability and how new, sustainable fibres overcome those issues. Finally it discusses the challenges and implications of these sustainable fibres on technical and economic fronts.